A virtual environment authoring interface for content-expert authors - Tangkuampien, Jakkaphan (Department of Computer Science, 2024)
[pg 47 missing] Since the advent of virtual reality (VR), the technology has been exploited in many areas to aid information transfer. In this respect, virtual reality can be regarded as a medium across which authors can communicate with a target group. However, many experts in non-computer-related areas, looking to exploit VR often come unstuck trying to take advantage of this medium. In these cases, one cannot blame these content-expert authors as they have successfully exploited other media prior to VR. On the other hand, the fault can not lie with the medium itself since it has been effectively exploited by other groups of authors. One probable cause could be the authoring tools themselves, or rather their interfaces to be more accurate. A tool's authoring interface is the only access point into the VR medium and one can only assume that the interfaces are not doing their job effectively. Our study was aimed at investigating authoring interfaces especially from the point of view of content-expert authors. Our approach was to involve such authors who have been able to master existing authoring tool mostly on their own. These authors were in a unique position - having managed to overcome initial difficulties, they have come to understand the inner working of the medium itself. The study was also well-suited to the appreciative inquiry (AI) methodology - a community-centric methodology that has rarely been applied in the area of computer science. Appreciative inquiry, with its root in action research, encourages a similar spiral-based methodology but with positive approach in all phases. With a group of content-expert VR authors, we applied a cycle of AI, resulting first in a list of interface issues that required some attention as well as some idea of how they can be resolved. The second phase of AI involved working closely with the authors to come up with resolution strategies to each of these issues. These solutions were then assessed for the level at which they have addressed their respective issue by another group of content-expert authors. Finally, an online survey was conducted to extend our results to the wider population of content-expert authors. The survey results confirmed that the interface issues discovered applied to the general population and that the proposed solutions were generally thought to be advantageous to the authoring process. Additionally, these positive results were encouraging since it means that our adaptation of AI was successful.